The Effectiveness of Sport Massage In Reducing Doms Pain In Athletes: Literature Review - Fikri Ramdhan, Ghozul; Aziza Kusuma, Rhona; Guntur Putri, Shavira; Nur Alpiah , Dini (Worldwide Research Publishing, 2024)
When you do excessive exercise, you may start to feel pain in the muscles you use, such as your joints, bones and limbs. Complaints of pain or soreness caused by excessive exercise are called delayed onset muscle soreness (DOMS). The aim of this study was to determine the effectiveness of sports massage in reducing pain in doms. This study used a literature review approach. A literature review is a comprehensive analysis (not just a summary) of scientific documents directly related to a research question. The literature review was carried out using PICO searches in several databases such as Google Scholar. Criteria were met in 5 reviews that reported sports massage performed 3 times a week for 4 weeks for 20 minutes with moderate pressure (2 cm depth). Of the several articles found, most used RCTs, quasi-experimental study designs and clinical trials with P<0.05. Both the experimental and control groups received sports massage. It can be concluded that sports massage is effective in speeding up the athlete's recovery process.